PENGARUH REBUSAN DAUN SIRIH MERAH TERHADAP WAKTU PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM - Esther Lenny Dorlan Marisi; Nur Hikmah Hasanah (NHM PRESS, 2023)
Background : Background: One of it was causing maternal mortality (MMR) is caused by infection of the perineal wound that occurs during and after childbirth. A perineal tear is an obstetric injury and varies in severity. One of the non-pharmacological treatments this problem is red betel leaf. Objective: to obtain the influent of red betel leaf decoction on healing time of perineal wounds in post partum from previous researchers. Method: literature review using data sources obtained from searching the google scholar database, according to research topics in 2017-2021 (post partum, perineal wounds, red betel leaf) with PICOTS analysis. Results: the posttest showed that the wound healing time was less than 5 days in the intervention group, while in the control group the healing time was more than 5 days and p_value <0.05 which means that there is a significant influent perineal wound healing in postpartum after being given a decoction intervention. red betel leaf Conclusion: Decoction of red betel leaf can influent the healing time of perineal wounds in postpartum. Suggestion: The next research is to examine the time of perineal wound healing in postpartum mothers by using different independent variables.